Monetary Policy and Liquidity of Vietnam’s Stock Market - Tran, Thi Hai Ly (University of Economics Ho Chi Minh City, 2023)
This study investigates the impact of monetary policy on liquidity of Vietnam’s stock market from September 2007 to November 2014. Time series of liquidity are determined by monthly liquidity data for 643 enterprises in the surveyed period. Two variables of the monetary policy, including growth in money supply and interbank rate, are employed in VAR model along with four different measures of market liquidity. The results show that unexpected variance in the two monetary policy variables has no significant impact on the market liquidity, which, in turn, may be improved by the positive shocks of market returns, inflation, and growth in industrial production. Market variance does produce certain effects, but discrepancies occur in the signs of various liquidity measures.